Long-term cardiometabolic health in people born after assisted reproductive technology: a multi-cohort analysis. (6th February 2023) - Elhakeem, Ahmed; Taylor, Amy E; Inskip, Hazel M; Huang, Jonathan Y; Mansell, Toby; Rodrigues, Carina; Asta, Federica; Blaauwendraad, Sophia M; Håberg, Siri E; Halliday, Jane; Harskamp-van Ginkel, Margreet W; He, Jian-Rong; et al.
Structured Graphical Abstract: Structured Graphical Abstract Meta-analysis of results in 35000 offspring with cardiometabolic outcomes measured at various ages found no robust differences in blood pressure, heart rate, triglycerides, or hyperglycaemic/insulin resistance traits, and higher cholesterol in ART-conceived than NC offspring. Analysis of cardiometabolic trajectories up to age 26 years in 17, 000 offspring identified subtle increases to nominally higher blood pressure and triglycerides in young adults who were conceived by ART. ART, assisted reproductive technology; NC, natural conception; SBP, systolic blood pressure; DBP, diastolic blood pressure; HR, heart rate; TC, total cholesterol; HDLc, high-density lipoprotein cholesterol; LDLc, low-density lipoprotein cholesterol; TG, triglycerides; HbA1c, glycated haemoglobin. Abstract: Aims: To examine associations of assisted reproductive technology (ART) conception (vs. natural conception: NC) with offspring cardiometabolic health outcomes and whether these differ with age. Methods and results: Differences in systolic (SBP) and diastolic blood pressure (DBP), heart rate (HR), lipids, and hyperglycaemic/insulin resistance markers were examined using multiple linear regression models in 14 population-based birth cohorts in Europe, Australia, and Singapore, and results were combined using meta-analysis. Change in cardiometabolic outcomes from 2 to 26 years was examined using trajectory modelling of four cohorts with repeated measures. 35 938 (654 ART) offspring were included in the meta-analysis. Mean age ranged from 13 months to 27.4 years but was <10 years in 11/14 cohorts. Meta-analysis found no statistical difference (ART minus NC) in SBP (−0.53 mmHg; 95% CI:−1.59 to 0.53), DBP (−0.24 mmHg; −0.83 to 0.35), or HR (0.02 beat/min; −0.91 to 0.94). Total cholesterol (2.59%; 0.10–5.07), HDL cholesterol (4.16%; 2.52–5.81), LDL cholesterol (4.95%; 0.47–9.43) were statistically significantly higher in ART-conceived vs. NC offspring. No statistical difference was seen for triglycerides (TG), glucose, insulin, and glycated haemoglobin. Long-term follow-up of 17 244 (244 ART) births identified statistically significant associations between ART and lower predicted SBP/DBP in childhood, and subtle trajectories to higher SBP and TG in young adulthood; however, most differences were not statistically significant. Conclusion: These findings of small and statistically non-significant differences in offspring cardiometabolic outcomes should reassure people receiving ART. Longer-term follow-up is warranted to investigate changes over adulthood in the risks of hypertension, dyslipidaemia, and preclinical and clinical cardiovascular disease.